Land Use Changes Affecting Soil Organic Matter Accumulation in Topsoil and Subsoil in Northeast Thailand. (24th June 2020) - Kunlanit, Benjapon; Khwanchum, Laksanara; Vityakon, Patma
Abstract : The objectives of this study were to investigate effects of land use on accumulation of soil organic matter (SOM) in the soil profile (0–100 cm) and to determine pattern of SOM stock distribution in soil profiles. Soil samples were collected from five soil depths at 20 cm intervals from 0 to 100 cm under four adjacent land uses including forest, cassava, sugarcane, and paddy lands located in six districts of Maha Sarakham province in the Northeast of Thailand. When considering SOM stock among different land uses in all locations, forest soils had significantly higher total SOM stocks in 0–100 cm (193 Mg·C·ha −1 ) than those in cassava, sugarcane, and paddy soils in all locations. Leaf litter and remaining rice stover on soil surfaces resulted in a higher amount of SOM stocks in topsoil (0–20 cm) than subsoil (20–100 cm) in some forest and paddy land uses. General pattern of SOM stock distribution in soil profiles was such that the SOM stock declined with soil depth. Although SOM stocks decreased with depth, the subsoil stock contributes to longer term storage of C than topsoils as they are more stabilized through adsorption onto clay fraction in finer textured subsoil than those of the topsoils. Agricultural practices, notably applications of organic materials, such as cattle manure, could increase subsoil SOM stock as found in some agricultural land uses (cassava and sugarcane) in some location in our study. Upland agricultural land uses, notably cassava, caused high rate of soil degradation. To restore soil fertility of these agricultural lands, appropriate agronomic practices including application of organic soil amendments, return of crop residues, and reduction of soil disturbance to increase and maintain SOM stock, should be practiced.